Rab11 is required for embryonic nervous system development in Drosophila. - Bhuin, T.; Roy, J.K. (Cell and Tissue Research, 2009)
In eukaryotes, membrane trafficking is regulated by the small monomeric GTPases of Rab protein family. Rab11, an evolutionary conserved, ubiquitously expressed subfamily of the Rab GTPases, has been implicated in the regulation of vesicular trafficking through the recycling of endosomes. To dissect out the role of this protein during embryonic nervous system development, we have studied the expression pattern of Rab11 in the ventral nerve cord during neuronal differentiation in the Drosophila embryo. When the dominant-negative or constitutively-active mutant DRab11 proteins are expressed in neurons, or when homozygous mutant Rab11 embryos are analyzed, defects are found in the developing central nervous system, along with disorganization and misrouting of embryonic axons. Our results provide the first in vivo evidence that Rab11 is involved in the development of the nervous system during Drosophila embryogenesis.